(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Revenue is one of the most important financial statement measures to both preparers and users of financial statement. It is used to measure and assess aspects of reporting entity’s past financial performance, future prospects, and financial health. The pharmaceutical and life sciences industry includes a number of sub-sectors, the largest being pharmaceutical, biotechnology, contract research organization, and medical devices. The common feature is that each sub-sector develops, produces, and market a diverse array products, technology, and services that relate to human health. Measurement of revenue issues arise not only from the sale of drugs and medical devices, but increasingly from arrangement between companies in the industry to develop and bring products to market. Companies in the pharmaceutical and life sciences industry often enter in to arrangement to develop drugs, either as a supplier of services, consumer of those services, or through execution of licence arrangements. These complex transactions are accounted for under the revenue standard (IFRS 15, Revenue from contracts with customers). This paper focuses on how the revenue standards will impact companies in the pharmaceutical and life sciences industry and contrasts the guidance with current practice under IFRS.